Electrocardiogram analysis in Anderson-Fabry disease: a valuable tool for progressive phenotypic expression tracking - Parisi, V.; Baldassarre, R.; Ferrara, V.; Ditaranto, R.; Barlocco, F.; Lillo, R.; Re, F.; Marchi, G.; Chiti, C.; Di Nicola, F.; Catalano, C.; Barile, L.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Electrocardiogram (ECG) has proven to be useful for early detection of cardiac involvement in Anderson-Fabry disease (AFD); however, little evidence is available on the association between ECG alterations and the progression of the disease. Aim and Methods To perform a cross sectional comparison of ECG abnormalities throughout different left ventricular hypertrophy (LVH) severity subgroups, providing ECG patterns specific of the progressive AFD stages. 189 AFD patients from a multicenter cohort underwent comprehensive ECG analysis, echocardiography, and clinical evaluation. Results The study cohort (39% males, median age 47 years, 68% classical AFD) was divided into 4 groups according to different degree of left ventricular (LV) thickness: group A ≤ 9 mm (n = 52, 28%); group B 10–14 mm (n = 76, 40%); group C 15–19 mm (n = 46, 24%); group D ≥ 20 mm (n = 15, 8%). The most frequent conduction delay was right bundle branch block (RBBB), incomplete in groups B and C (20%,22%) and complete RBBB in group D (54%, p < 0.001); none of the patients had left bundle branch block (LBBB). Left anterior fascicular block, LVH criteria, negative T waves, ST depression were more common in the advanced stages of the disease (p < 0.001). Summarizing our results, we suggested ECG patterns representative of the different AFD stages as assessed by the increases in LV thickness over time (Central Figure). Patients from group A showed mostly a normal ECG (77%) or minor anomalies like LVH criteria (8%) and delta wave/slurred QR onset + borderline PR (8%). Differently, patients from groups B and C exhibited more heterogeneous ECG patterns: LVH (17%; 7% respectively); LVH + LV strain (9%; 17%); incomplete RBBB + repolarization abnormalities (8%; 9%), more frequently associated with LVH criteria in group C than B (8%; 15%). Finally, patients from group D showed very peculiar ECG patterns, represented by complete RBBB + LVH and repolarization abnormalities (40%), sometimes associated with QRS fragmentation (13%). Conclusions ECG is a sensitive tool for early identification and long-term monitoring of cardiac involvement in patients with AFD, providing “instantaneous pictures” along the natural history of AFD. Whether ECG changes may be associated with clinical events remains to be determined.